Application of the Legal Maxim of Al-Ashl fi Al-Ibdha ‘al-Tahrim to the Phenomena of Homosexuality - Syarifudin Syarifudin (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2022)
This research examines the phenomenon of homosexuality that is currently developing in the Western world and has even entered Indonesia. Many homosexual associations and organizations established in Europe and America, even in Indonesia are known as LGBT (Lesbian, Gay, Bisexual, and Transgender). Yet homosexuality is an extraordinary moral crime and a sign of moral degradation. The application of the principles of fiqh “Al-Ashl fi Al-Ibdha’ al-Tahrim” (the original law on sex is haram) in responding to the homosexual phenomenon through the approach of maqasid syari’ah, then homosexuality is haram because it destroys religion, the human soul, reason, descent, and also destroy honor. The original law of jurisprudence on the issue of sex is haram, responding to the homosexual phenomenon that is against the teachings of Islam which requires marriage to the opposite sex. Of course homosexual offenders or even more broadly, LGBT (Lesbian, Gay, Bisexual, and Transgender) are always looking for justifications and arguments that justify these acts, even on human rights grounds. Even though this is very contrary to his nature as a human being.